Evaluation of a quality system developed for pharmacy teaching laboratories - Terribile, Corinne Muscat; Wirth, Francesca; Zammit, Marie Clare; Vella, Janis; Azzopardi, Lilian M; Serracino-Inglott, Anthony (Pharmacy Education, 2013)
Background: The implementation of a quality system improves the educational quality of activities undertaken in a laboratory. Aim: To evaluate the perception of undergraduate pharmacy students and laboratory demonstrators on the quality system implemented in the laboratories of the Department of Pharmacy at the University of Malta. Method: A self-administered questionnaire was developed, psychometrically evaluated and distributed to second, third and fourth year undergraduate pharmacy students and laboratory demonstrators (N=110). Results: Out of a total of 94 questionnaires collected, 91 participants agreed that the implemented quality system is important to carry out procedures correctly and safely in the laboratory and is a helpful educational tool for students to appreciate quality processes in pharmacy (n=84). Ninety two participants agreed that standard operating procedures are an essential aspect of a quality system and are important educational tools for laboratory work (n=73). Conclusion: The implemented laboratory quality system is a valuable educational tool for pharmacy students.